2016
DOI: 10.1016/j.atherosclerosis.2016.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Innate immune cell activation and epigenetic remodeling in symptomatic and asymptomatic atherosclerosis in humans in vivo

Abstract: Circulating monocytes of patients with symptomatic, but not asymptomatic, atherosclerosis have a pro-inflammatory phenotype and increased expression of glycolytic enzymes, associated with epigenetic remodeling at the level of histone methylation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
145
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(165 citation statements)
references
References 27 publications
10
145
0
4
Order By: Relevance
“…To further elucidate the role of trained immunity in the development of these disorders, we assessed the inflammatory phenotype of monocytes isolated from patients with severe symptomatic coronary atherosclerosis. We demonstrated that monocytes from patients with symptomatic carotid atherosclerosis show an increased production of IL‐1β upon ex vivo stimulation with LPS for 24 hours compared to controls . Baseline RNA expression of IL‐1β and IL‐1RA was significantly higher in these patients compared to controls.…”
Section: The Role Of Il‐1 In Trained Immunitymentioning
confidence: 80%
See 1 more Smart Citation
“…To further elucidate the role of trained immunity in the development of these disorders, we assessed the inflammatory phenotype of monocytes isolated from patients with severe symptomatic coronary atherosclerosis. We demonstrated that monocytes from patients with symptomatic carotid atherosclerosis show an increased production of IL‐1β upon ex vivo stimulation with LPS for 24 hours compared to controls . Baseline RNA expression of IL‐1β and IL‐1RA was significantly higher in these patients compared to controls.…”
Section: The Role Of Il‐1 In Trained Immunitymentioning
confidence: 80%
“…Similar to β‐glucan‐ and BCG‐induced trained monocytes, glycolysis was shown to be increased in symptomatic CAD patients. Interestingly, the expression levels of IL‐1β significantly correlated with the expression of the two rate limiting enzymes in the glycolysis pathway, hexokinase 2 (HK2) and 6‐phosphofructo‐2‐kinase/fructose‐2,6‐biphosphatase 3 (PFKFB3) . Since many clinical as well as experimental studies have shown that IL‐1β plays a key role in the progression of atherosclerosis, the enhanced production of IL‐1 as a result of trained innate immunity programs might be an important process contributing to the development of atherosclerosis.…”
Section: The Role Of Il‐1 In Trained Immunitymentioning
confidence: 99%
“…A similar finding has been found by comparing monocytes from subjects with symptomatic vs . asymptomatic carotid atherosclerosis (Bekkering et al, 2016). Another study shows that HDAC3 inhibitors increase the expression of ABCA1 and ABCG1 in cultured macrophages and that myeloid deletion of HDAC3 in Western diet-fed Ldlr -/- mice suppresses atherosclerosis and promotes a more resolving phenotype in lesional macrophages (Hoeksema et al, 2014).…”
Section: Inflammatory Macrophages Drive Atherosclerosis Progressionmentioning
confidence: 99%
“…Another challenge to treating chronic autoimmune diseases is the accumulation of autoreactive tissue resident memory lymphocytes whose pathogenic phenotypes are stabilized by epigenetic modifications of various gene loci (Phan et al, 2017). There is also evidence that metabolic conditions can induce epigenetic changes in macrophages, leading to a form of innate immune memory (“trained immunity”) (Netea et al, 2016; Phan et al, 2017) that may promote lesion progression (Bekkering et al, 2016). In this regard, pre-clinical studies have provided support for the principal that targeting physiologic epigenetic modifiers, for example with inhibitors of Bromodomain and Extra-Terminal motif (BET) proteins, can inhibit inflammatory gene expression and reduce atherosclerosis (Brown et al, 2014; Jahagirdar et al, 2014).…”
Section: Summary and Therapeutic Considerationsmentioning
confidence: 99%
“…Molecular and cellular mechanisms involved in this phenomenon are still not fully understood. It is believed that the main mechanism underlying enhanced responses involves epigenetic reprogramming, which in turn may entail altered pattern recognition receptors’ expression, metabolic reprogramming, or/and altered cytokines release (Saeed et al, 2014; Bekkering et al, 2016b). Long-term epigenetic changes in monocytes and macrophages apparently involve both histone methylation and acetylation, as for instance H3K4 monomethylation and H3K27 acetylation induced by LPS (Ostuni et al, 2013; Saeed et al, 2014), and histone H3K4 trimethylation and H3K27 acetylation caused by β-glucan (Quintin et al, 2012; Saeed et al, 2014).…”
Section: Introductionmentioning
confidence: 99%